An exploration of the deficiencies in the Modern Slavery Act 2015 from an operational victim-centred perspective - Austin, Lucy Annabel (2023)
The Modern Slavery Act 2015 (MSA 2015), set out to make provisions in four areas centring around the common goal of the prevention of exploitation. The four provisions targeted slavery, servitude and forced or compulsory labour; human trafficking; to make provision for an Anti-slavery Commissioner (IASC); and for connected purposes. The UK did so largely in order to fulfil its international obligations under the Palermo Protocol and European Convention on Action against Trafficking (ECAT). Additionally, Home Secretary Theresa May placed the issue at the forefront of the Government's policy agenda, highlighting new research in 2013 which revealed the number of potential victims of exploitation in the UK to be between 10,000 – 13,000. The MSA 2015 sought to produce a full coverage provision of the area of exploitation. The goals of the Act were to protect victims by increasing prosecutions, which would be achieved by ensuring that law enforcement and the courts have the authority to do so. Home Secretary Theresa May said “The Bill … will ensure that we can effectively prosecute perpetrators, properly punish offenders and help prevent more crimes from taking place. Most crucially, it will enhance protection and support for the victims of these dreadful crimes”. From inception it has been the victims of this crime that have been the driving force, the number of potential victims was both shocking to the public and furthermore a rhetorical tool that was repeated regularly when pushing this Bill through Parliament and into law. Therefore, if not for the victims, then for whom is this Act for? In approaching this paper, I posed the same question and determined that the victims of modern slavery should be at the centre of my examination of the MSA 2015 from an operational perspective. This research seeks to give a comprehensive view of the operational reality of working with the MSA 2015 from identification, to support and finally to the judicial process. Despite these aspects being explored individually, this thesis seeks to plug the gap in coalescing these aspects and providing a policy focused thesis that communicates the current literature position which is informed by interviews and surveys from current front line workers.